2020
DOI: 10.1002/lary.28643
|View full text |Cite
|
Sign up to set email alerts
|

H+/K+ATPase Expression in the Larynx of Laryngopharyngeal Reflux and Laryngeal Cancer Patients

Abstract: Objectives The gastric H+/K+ ATPase proton pump has previously been shown to be expressed in the human larynx, however its contribution to laryngopharyngeal reflux (LPR) signs, symptoms and associated diseases such as laryngeal cancer is unknown. Proton pump expression in the larynx of patients with LPR and laryngeal cancer was investigated herein. A human hypopharyngeal cell line expressing the proton pump was generated to investigate its effects. Study Design In‐vitro translational. Methods Laryngeal biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…Zhang et al of the H + /K + ATPase α-and β-subunits in the stomach among different human tissues evaluated, including the larynx. 48 The above-cited studies provide convincing evidence of a laryngeal H + /K + ATPase [42][43][44][45][46][47] in normal laryngeal tissues but also suggest the potential role of the proton pump in the abnormal mucus secretion frequently seen in patients with chronic laryngitis. The discovery of a laryngeal proton pump may explain the pathologically acidic environment of the oropharynx in patients without gastroesophageal reflux, with profound implications for PPI therapy, as the larynx is one of the extragastric targets of these drugs.…”
Section: Dovepressmentioning
confidence: 92%
See 1 more Smart Citation
“…Zhang et al of the H + /K + ATPase α-and β-subunits in the stomach among different human tissues evaluated, including the larynx. 48 The above-cited studies provide convincing evidence of a laryngeal H + /K + ATPase [42][43][44][45][46][47] in normal laryngeal tissues but also suggest the potential role of the proton pump in the abnormal mucus secretion frequently seen in patients with chronic laryngitis. The discovery of a laryngeal proton pump may explain the pathologically acidic environment of the oropharynx in patients without gastroesophageal reflux, with profound implications for PPI therapy, as the larynx is one of the extragastric targets of these drugs.…”
Section: Dovepressmentioning
confidence: 92%
“…Although its small sample size and absence of a reflux and laryngeal cancer-free control cohort, they suggested that acid secretion by functional H + /K + ATPase proton pumps expressed in laryngeal mucosa may elicit laryngeal mucosa cells and molecular changes associated with inflammation and cancerogenesis. 47…”
Section: Dovepressmentioning
confidence: 99%
“…1 Laryngopharyngeal reflux (LPR) has recently received attention in the context of laryngeal lesions, including vocal cord leukoplakia. 4-10…”
mentioning
confidence: 99%
“…Виявлені в роботі морфологічні зміни при ЛФР є досить закономірними з огляду на рівень рН та дію ферментів. Раніше було показа но, що за умов рефлюксу в слизовій обо лон ці гортані зростає експресія та ензиматична активність матриксної металопротеїнази-7 [20] при порушенні експресії Е-кадгерину, H + ,K + -ATФази та карбоангідрази ІІІ [21]. Це обмежує бар'єрні властивості покривного епітелію та сприяє розвитку ушкодження та хронічного запалення.…”
Section: результати та їх обговоренняunclassified